Sino-Indo Muslim Cultures: Tracing the History and Legacy of Cheng Ho and Chinese Muslims in Nusantara - Sumanto Al Qurtuby (Islam Nusantara: Journal for the Study of Islamic History and Culture, 2026)
This study re-examines the formation of Muslim communities in the Malay–Indonesian world through the presence of Zheng He, with particular attention to the role of Chinese Muslim networks in the early history of Islam in Indonesia. Employing a qualitative approach grounded in historical and library-based research, the study focuses its analysis on Javanese historical evidence related to diplomacy, maritime networks, and religious life prior to the period of European expansion. The findings demonstrate that Chinese Muslim networks were deeply embedded in diplomatic relations, maritime trade, and religious practices in the archipelago from an early period. Chinese Muslim influences contributed to the shaping of local Islamic practices while also broadening the cultural horizons of early Muslim communities in the region. A reassessment of several dominant Islamization theories further suggests that Sino-Indonesian Muslim interactions provide strong grounds for recognizing the “Chinese theory” as an important perspective alongside Arab, Persian, and Indian theories. This article makes a significant contribution to scholarship on Islamization and the history of Islam in the Malay–Indonesian world by affirming the plural genealogies of Indonesian Islam and enriching analytical frameworks on diaspora, mobility, and intercultural exchange in the making of Muslim societies in Nusantara.